Pengaruh Moral, Sosialisasi, Kesadaran, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Online - Fiqih Adillah; Tresno Eka Jaya; Hera Khairunnisa (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This study aims to analyze the influence of tax morale, tax socialization, taxpayer awareness, and tax sanctions on taxpayer compliance among online business actors. This study is motivated by the low tax revenue in the digital sector, which is not comparable to the rapid growth of e-commerce transactions and the increasing number of online business actors every year. Quantitative research methods were applied using multiple linear regression analysis with SPSS version 25. Data were collected through structured questionnaires distributed to 300 online business actors in East Jakarta. The results of the study indicate that tax morale and tax socialization have a positive influence on taxpayer compliance. However, taxpayer awareness and tax sanctions do not affect taxpayer compliance. Further research is recommended to expand the respondents and include additional variables related to external factors to obtain more comprehensive results.